Capability Development among the Ultra-poor in Bangladesh: A Case Study (Journal of Health, Population and Nutrition, 2009)
Microcredit is advocated as a development tool that has the potential to reduce poverty, empower participants, and improve health. Results of several studies have shown that the extreme poor, or the ultra-poor, often are unable to benefit from traditional microcredit programmes and can, as a result of taking a loan they cannot repay, sink deeper into economic and social poverty. This case study describes an intervention directed at enabling the ultra-poor rural populations to pull themselves out of poverty. The intervention integrates multiple components, including asset grants for income generation, skills training, a time-bound monthly stipend for subsistence, social development and mobilization of local elite, and health support. Results of an evaluation showed that, after 18 months, the programme positively impacted livelihood, economic, social and health status to the extent that 63% of households (n=5,000) maintained asset growth and joined (or intended to join) a regular microcredit programme. Impacts included improved income, improved food security, and improved health knowledge and behaviour. Applying a social exclusion framework to the intervention helps identify the different dynamic forces that can exclude or include the ultrapoor in Bangladesh in development interventions such as microcredit. Key words: Capacity-building; Economic assistance; Poverty; Ultra-poor; Bangladesh   doi: 10.3329/jhpn.v27i4.3399 J Health Popul Nutr 2009 Aug;27(4):528-535